P111 CLINICAL PROFILE AND CORONARY ANGIOGRAPHIC FINDINGS IN A PATIENT POPULATION WITH NORMAL STRESS ECHOCARDIOGRAPHY AND ANGINAL SYMPTOMS AND/OR ELECTROCARDIOGRAM ABNORMALITIES INDUCED BY THE STRESS TEST. (18th May 2022) - Spinelli, A; Cianfrocca, C; Di Fusco, S; Di Michele, S; Speciale, G; Auriti, A; Imperoli, G; Colivicchi, F
Abstract: : Patients with normal pharmacologic stress echocardiography (SE) imaging but anginal symptoms and/or electrocardiographic (ECG) abnormalities induced by the stress test are commonly encountered in clinical practice. The aim of this study: was to report the clinical profile of these patients and the coronary angiographic findings observed in this setting. Methods: We analysed pharmacologic SE results of all patients who underwent this examination at our centre between 2015 and 2020. 34 (74%) patients performed pharmacological SE with dipyridamole and 11 (24%) with dobutamine. All patients with normal SE imaging and anginal symptoms and/or ECG abnormalities triggered by this examination who required further diagnostics using coronary angiography were enrolled in this study. Patient data were retrospectively collected from hospital records. Results: 1553 SEs were performed from 2015 to 2020. Forty–five patients met the inclusion criteria of our study (62% female, mean age 67 years). The majority of included patients 37 (82%) had hypertension, 22 (49%) dyslipidemia, 13 (29%) diabetes and 7 (16%) were smokers. Thirteen patients (29%) had anginal symptoms induced by SE and positive coronary angiography. Six patients (13%) had ECG abnormalities and positive coronary angiography. Only two patients (4%) had both ECG abnormalities, anginal symptoms, and positive coronary angiography. Overall, 47% of patients had positive coronary angiography, half of whom had a history of ischemic heart disease. Seventeen patients (38%) had anginal symptoms and negative CVG. Two patients (4%) had ECG abnormalities and negative CVG. Five patients (11%) had both ECG abnormalities and anginal symptoms (Table 1). Overall, 53% of patients had negative CVG. Conclusion: In our centre, more than half of patients with normal SE imaging associated with ECG abnormalities and anginal symptoms induced by the stress test had negative coronary angiography. Hypertension was the most common risk factor in this patient population.